1975
DOI: 10.1159/000180432
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Extrarenal Elimination of Uric Acid in Man

Abstract: The origin of uric acid, metabolic pathways of purine metabolism and the disposition of uric acid in normal man are reviewed. Two thirds of the uric acid is normally excreted through the kidney while one third gains entrance to the gut where it undergoes uricolysis. The pathogenesis of hyperuricemia in primary and secondary gout is discussed. Increased production or decreased excretion of uric acid are the two principal mechanisms of hyperuricemia. The known biochemical defects associated with primary overprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
6

Year Published

1975
1975
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(67 citation statements)
references
References 14 publications
1
60
0
6
Order By: Relevance
“…In vitro studies of purine absorption in the hamster have shown that hypoxantine, xanthine and to a lesser extent uric acid are preferentially excreted rather than absorbed across the intestine (Berlin and Hawkins, 1968), while studies in sheep have indicated that the capacity of the small intestine to absorb allantoin is limited (Chen et al, 1990b). Nucleic acids, free bases (except xanthine) and PDs entering the large intestine do not appear to be absorbed due to extensive degradation by indigenous microbes (Sorensen, 1960;Ellis and Bleichner, 1969a;Chen et al, 1990a), and therefore purines excreted in faeces appear to be primarily derived from microbes residing in the caecum (Surra et al, 1997b). Furthermore, variations in the supply of NAs entering the caecum and the extent of hindgut fermentation do not appear to affect urinary PD excretion, but there is evidence to suggest that it is positively influenced by the flow of undigested fibre in the duodenum (Surra et al, 1997b).…”
Section: Digestion Of Nucleic Acidsmentioning
confidence: 99%
“…In vitro studies of purine absorption in the hamster have shown that hypoxantine, xanthine and to a lesser extent uric acid are preferentially excreted rather than absorbed across the intestine (Berlin and Hawkins, 1968), while studies in sheep have indicated that the capacity of the small intestine to absorb allantoin is limited (Chen et al, 1990b). Nucleic acids, free bases (except xanthine) and PDs entering the large intestine do not appear to be absorbed due to extensive degradation by indigenous microbes (Sorensen, 1960;Ellis and Bleichner, 1969a;Chen et al, 1990a), and therefore purines excreted in faeces appear to be primarily derived from microbes residing in the caecum (Surra et al, 1997b). Furthermore, variations in the supply of NAs entering the caecum and the extent of hindgut fermentation do not appear to affect urinary PD excretion, but there is evidence to suggest that it is positively influenced by the flow of undigested fibre in the duodenum (Surra et al, 1997b).…”
Section: Digestion Of Nucleic Acidsmentioning
confidence: 99%
“…In adult humans approximately two-thirds of the uric acid is eliminated through the kidneys and one-third through the gastrointestinal tract (16). Renal handling of uric acid seems to involve four steps: glomerular filtration, tubular reabsorption, active secretion, and postsecretory reabsorption (17).…”
Section: Metabolismmentioning
confidence: 99%
“…The magnitude of purine loss can be between 5% and 9% of the resting muscle ATP content (Bangsbo et al 1992;Hellsten et al 1999). It has been reported that the plasma purines are excreted in the urine (Nasrallah and Al Khalidi 1964;Sutton et al 1980;Stathis et al 1999), or converted to uric acid (Hellsten et al 1994) and subsequently excreted (Nasrallah and Al Khalidi 1964;Sorensen and Levinson 1975;Stathis et al 1999). Sorensen and Levison (1975) demonstrated that, in a resting individual, the uric acid loss via the gut is one third, whilst via the urine is two thirds of the total uric acid loss in the untrained individual.…”
Section: Introductionmentioning
confidence: 99%